Characterization of Herbal Tea Bags Made from Starfruit Leaves (Averrhoa Bilimbi), Gotu Kola Leaves (Centella Asiatica) and Cinnamon Powder (Cinnamomun Burmanii) as Functional Drinks - Fachrur Rozi; Diana Silvy; Daimon Syukri (Lembaga Penelitian dan Pengabdian, Universitas Andalas, 2022)
This research aimed to study the characteristics of herbal tea bags from starfruit leaves, gotu kola leaves and cinnamon powder. This research used a completely randomized design with 5 treatments, namely differences in substitution of cinnamon powder 0%, 1%, 2%, 3% and 4% with 3 replications. The data obtained were analyzed statistically with ANOVA (Analysis of Variance) and if they were significantly different, then continued with the DNMRT (Duncan's News Multiple Range Test) test at a level of 5%. The results showed that the difference in the amount of cinnamon powder substitution had a significant effect on antioxidant activity, total water-soluble ingredients, total polyphenols, color, taste, and aroma. Differences in the concentration of cinnamon powder substitution did not significantly affect the water content and pH. The best treatment in this research was treatment E with substitution of cinnamon powder 4%. The results of organoleptic analysis were the average value of colour preference 3.95, taste 3.65, and aroma 4. The results of chemical analysis were pH 6.13 and antioxidant activity 36.93%.